Low income housing allocation system in Malaysia: managing housing need for the poor - Shuid, Syafiee (2010)
Since early 1990s, Malaysia experienced rapid urbanization in line with continuous economic growth. Despite various housing programmes implemented by the Malaysian government together with private sector to provide housing for the low income people but the number of squatter settlements continue to grow. In 1999, the total people living in squatter is more than half of million including the illegal immigrants from the neighbouring countries. The government began to increased number of new housing stock in order to resolve the issue. However the government later realized the issue is no longer related to housing production but due to inefficient allocation system. Many studies indicated problem faced by the low income people to purchase the house due to bureaucratic process and corruption practices among the bureaucrats and politicians in housing allocation. Thus, in 1997 the Computerised Open Registration System (ORS) for low cost housing allocation was introduced by the government to provide efficient and more transparent system of allocation. The system not only used to allocate the house for sale built by the government but also those built by the private sector. Finally the system not only to ensure the targeted people will eventually owned the low cost house but also to reduce corruption which is common problem in developing countries.